Rancang Bangun Aplikasi Animasi Pembelajaran Matakuliah Teori Bahasa Otomata Pada Sekolah Tinggi Teknologi Pagar Alam - Oman Arrohman; Cornelia Tri Wahyuni (Jurnal Nasional Ilmu Komputer, 2022)
Abstract This study aims to design and develop an application for learning animations for Teori Bahasa Otomata courses at the Pagar Alam High School of Technology that attracts students' interest. The background of this research is learning that still uses conventional media which makes it difficult for teachers so that it takes a long time and makes students bored when learning takes place. The animation application for learning the Teori Bahasa Otomata course was developed using Adobe Flash Professional CS6 and Xampp applications as server software to the MySql database. This research uses the Design Development Implementation Evaluation (ADDIE) analysis system development method. Based on the results of the expert review that has been carried out, it shows an average value of 4.90 with a very valid category. Then based on the results of the field test or alpha and beta tests obtained from the results of the pretest and posttest the average student scored 87.0 in the High category. This shows an increase in learning outcomes before and after the use of Design and Build Animation Learning Teori Bahasa Otomata.